Points de vue conceptuel et politique chez Habermas - Patrick Chaskiel (Communication)
As Habermas’s project is to reconcile a conceptual point of view with one which is political-normative, it is legitimate to verify if these two points of view coincide. From this perspective, we can show that, when Habermas analyses the crisis of the nation-state, the binary conceptual model — system/lived word — slides toward a ternary one — autonomous and depoliticised economic sphere, democratic nation-state, and space of contestation. This movement and the difficulties it brings with it come notably from the idea that each sphere of society is supposedly integrated by a unique medium (money or power or discussion). Such a positions shows itself to be formally untenable. By relying of Habermas himself, it is possible to go beyond the principle of integration and adopt one of co-ordinated dissension within social relations.